Quality of life in health Iranian elderly population approach in health promotion: A systematic review - Mohsen Poursadeqiyan; Maryam Feiz Arefi; Amin Babaei Pouya; Mojtaba Jafari (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The quality of life (QOL) is essential in all different stages of life; however, It is more important for older people as it can be effective in promoting their health. Therefore, the present study aimed to review the literature on the QOL in the Iranian elderly population. MATERIALS AND METHODS: The study was carried out as a systematic review. For this purpose, all databases were searched in March 2021. The keywords used for the search were "quality of life, elderly, older adults, aging, seniors, and Iran" along with the Persian equivalents. PRISMA protocol was used to screen articles. After removing duplicate and irrelevant items, two evaluators appraised the articles separately based on a researcher-made checklist derived from the SBEM and STROBE Statement standard checklists. RESULTS: The initial search yielded 3734 studies on the QOL in the Iranian elderly population. After screening and assessing the studies based on inclusion and exclusion criteria, 22 articles remained in the study. Most of the studies (cross-sectional) were conducted in Tehran using a 36-item Short-Form Health Survey to assess the QOL. The studies investigated sociodemographic determinants, physical and health-related behaviors, and spirituality and psychological determinants of the QOL. The sociodemographic determinants were the most common factors under study. The results showed that the role of gender and socioeconomic status was the strongest among the sociodemographic characteristics. A significant association was found between the QOL in the Iranian elderly population and factors such as depression and religious confrontation. CONCLUSION: In addition to chronic diseases, diseases of the oral and dental, as well as an unhealthy diet, should be considered in the elderly. Therefore, attention should be paid to all social, physical, and psychological variables that affect the QOL of older people.